Enlargement of tilapia (Oreochromis niloticus) in swift water ponds at the Bedegung Fish Seed Center, Muara Enim, South Sumatera - Paradhiba, Aulia Marwah; Suhermansyah, Suhermansyah; Mukti, Retno Cahya (Acta Aquatica: Aquatic Sciences Journal, 2023)
Tilapia (Oreochromis niloticus) is a fish that is widely consumed by people in Indonesia. Market demand for tilapia increases every year, so tilapia production needs to be increased, especially in the process of rearing tilapia. This activity aims to determine the technique of rearing tilapia in swift water ponds on growth and survival. This activity is carried out from December 2021 to January 2022 at the Bedegung Fish Seed Center, Muara Enim. The method used in this activity is field observation and collection of primary and secondary data. The stages of implementing the activities include pond preparation, seed selection, seed stocking, fish rearing, and harvesting. The parameters observed were growth, feed efficiency, survival, and water quality. The results obtained were a growth in absolute weight of tilapia by 4.79 g; an absolute length of 6.5 cm; a feed efficiency of 74.24%; and survival of 94.93%. While the water quality values are temperature 23.1-25.8oC and pH 7.55-9.12.Keywords: Tilapia; Rearing; Swift water pons